2023
DOI: 10.1039/d3nj00228d
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable solutions for removing aged wax-based coatings from cultural heritage: exploiting hydrophobic deep eutectic solvents (DESs)

Abstract: Hydrophobic deep eutectic solvents as suitable alternatives to toxic solvents used in the conservation of Cultural Heritage sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…In addition to inhibitors, coating systems such as microcrystalline waxes are frequently used because they strike a balance between efficiency and aesthetic considerations [19][20][21]. However, one drawback of microcrystalline waxes is their relatively limited durability and poor outdoor protection, and issues such as dusting have been reported [22][23][24]. Consequently, as the need arose to address severe cases of corrosion, inhibitors, which were already known in the industrial sector, also found application in the realm of CH.…”
Section: Inhibitors For Cultural Heritage Metalsmentioning
confidence: 99%
“…In addition to inhibitors, coating systems such as microcrystalline waxes are frequently used because they strike a balance between efficiency and aesthetic considerations [19][20][21]. However, one drawback of microcrystalline waxes is their relatively limited durability and poor outdoor protection, and issues such as dusting have been reported [22][23][24]. Consequently, as the need arose to address severe cases of corrosion, inhibitors, which were already known in the industrial sector, also found application in the realm of CH.…”
Section: Inhibitors For Cultural Heritage Metalsmentioning
confidence: 99%
“…Based on these considerations, the ability of HDESs has been exploited for the removal of non-polar coatings, such as waxes, from art surfaces. The following HDESs were tested in laboratory using slide samples having a non-polar coating [11]. They were used to test the removal properties on beeswax and two microcrystalline waxes (R21 and Renaissance), commonly used in the past on stone and metal artifacts.…”
Section: Fig 4 After Dess Application (Above) and Four Months After A...mentioning
confidence: 99%
“…Recent advances in the study of greener formulations have introduced new sustainable solutions. However, despite the well-known hazards to human health and the environment posed by solvents like methylethylketone, aliphatic, and aromatic hydrocarbons, these substances continue to be widely used in common restoration practices [11][12][13][14][15][16][17][18]. This conservative approach can be attributed to conservators' initial skepticism towards innovative greener solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they can be more safely applied on various materials and only interact with other non-polar compounds. For this reason, they are commonly used to remove natural and microcrystalline waxes from artworks, such as outdoor stone and metal sculptures [5][6][7]15,[32][33][34]. Simultaneously, the removal of natural and synthetic varnishes, both aged A significant improvement was represented by the development of advanced colloidal systems, such as peelable and nanostructured chemical gels (Figure 2) [20,26,27].…”
Section: Introductionmentioning
confidence: 99%